Eruptive cycle and bubble trap of Strokkur Geyser, Iceland - Eibl, Eva P. S. (Prof. Dr.); Müller, Daniel (Dr.); Walter, Thomas R. (Dr. habil.); Allahbakhshi, Masoud; Jousset, Philippe (Dr.); Hersir, Gylfi Páll; Dahm, Torsten (Prof.) (Journal of Geophysical Research: Solid Earth, 2021)
The eruption frequency of geysers can be studied easily on the surface. However, details of the internal structure including possible water and gas filled chambers feeding eruptions and the driving mechanisms often remain elusive. We used a multidisciplinary network of seismometers, video cameras, water pressure sensors and one tiltmeter to study the eruptive cycle, internal structure, and mechanisms driving the eruptive cycle of Strokkur geyser in June 2018. An eruptive cycle at Strokkur always consists of four phases: (1) Eruption, (2) post-eruptive conduit refilling, (3) gas filling of the bubble trap, and (4) regular bubble collapse at shallow depth in the conduit. For a typical single eruption 19 +/- 4 bubble collapses occur in Phase 3 and 8 +/- 2 collapses in Phase 4 at a mean spacing of 1.52 +/- 0.29 and 24.5 +/- 5.9 s, respectively. These collapses release latent heat to the fluid in the bubble trap (Phase 3) and later to the fluid in the conduit (Phase 4). The latter eventually reaches thermodynamic conditions for an eruption. Single to sextuple eruptions have similar spacings between bubble collapses and are likely fed from the same bubble trap at 23.7 +/- 4.4 m depth, 13-23 m west of the conduit. However, the duration of the eruption and recharging phase linearly increases likely due to a larger water, gas and heat loss from the system. Our tremor data provides documented evidence for a bubble trap beneath a pool geyser.